2020
DOI: 10.15376/biores.15.2.2147-2162
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fresh water hyacinth with essential oil emulsion and subsequent use of the plant material for control of Aspergillus flavus on rice dessert products

Abstract: Essential oil emulsion, which is generally functionalized to have increased antifungal activity, has high solubility in water. The objective of this research was to develop an essential oil emulsion for absorption by water hyacinth plants in order to produce an essential oil absorbent material as a carrier of essential oil vapor that can be released to control mold in an enclosed packaging system. The fresh water hyacinth adsorbed the Michelia alba oil emulsion (100 µL/mL to 500 µL/mL) through its root system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similarly, Hazrati et al (2017) confirmed that seedling growth was related to essential oil dosage due to the electrolyte leakage observed when high doses were applied. In contrast, Songsamoe and Matan (2020) indicated that high concentrations of essential oil emulsion were better absorbed by hyacinth plant cells than low quantities. Therefore, the type of plant and seed stage affect the amount of essential oil to be used.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Hazrati et al (2017) confirmed that seedling growth was related to essential oil dosage due to the electrolyte leakage observed when high doses were applied. In contrast, Songsamoe and Matan (2020) indicated that high concentrations of essential oil emulsion were better absorbed by hyacinth plant cells than low quantities. Therefore, the type of plant and seed stage affect the amount of essential oil to be used.…”
Section: Discussionmentioning
confidence: 92%